Perancangan Sistem Pendaftaran Keanggotaan Unit Kegiatan Mahasiswa (UKM) di UIN SMDD Bukittinggi Berbasis Web - Jamaluddin Effendi Furqon (Journal of Information System and Education Development, 2024)
The registration system for prospective members of the Student Activity Unit (UKM) makes the registration process which is often held every period of time more effective and provides facilities to students who want to register themselves into the Student Activity Unit (UKM) organization that they are interested in in terms of completeness of information and coverage of information dissemination announcements when Open Recruitment is held in each UKM. With this website application also helps many organizations save their energy from material and also their time in designing an Open Recruitment that is designed using the PHP programming language and MySQL database. The purpose of this research is to design a registration system for prospective new members of the Student Activity Unit (UKM) around the campus of the State Islamic University Sjech M. Djamil Djambek Bukittinggi, so that students who want to register themselves into an organization on campus, namely UKM, can get all the information they need starting from registration information, schedule announcements, requirements, and much more in the hope of connecting the many UKM with students on campus.